2020
DOI: 10.1021/acs.molpharmaceut.0c00839
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Screening of α-Xylosides in Human Glioblastoma Cells

Abstract: Detailed experimental procedures, including chemical syntheses, MTT assays, IC 50 plots, and molecular modeling descriptions (PDF)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…For example, treatment of cells for 24 h with 0.3–1 mM 4-deoxy-4-fluoro-xyloside linked through a triazole to napthyl inhibited GAG biosynthesis by ∼ 80% [276] . Efforts are ongoing to generate prodrugs to achieve higher potency [277] . Caution should be exercised when using xyloside primers, as depletion of monosaccharides used in GAG biosynthesis can in some cases influence other glycosylation pathways.…”
Section: Glycosaminoglycan Inhibitorsmentioning
confidence: 99%
“…For example, treatment of cells for 24 h with 0.3–1 mM 4-deoxy-4-fluoro-xyloside linked through a triazole to napthyl inhibited GAG biosynthesis by ∼ 80% [276] . Efforts are ongoing to generate prodrugs to achieve higher potency [277] . Caution should be exercised when using xyloside primers, as depletion of monosaccharides used in GAG biosynthesis can in some cases influence other glycosylation pathways.…”
Section: Glycosaminoglycan Inhibitorsmentioning
confidence: 99%
“…It has also been reported the anti-angiogenic efficacy of two different fluoro-xylosides that by inhibiting HS synthesis in endothelial cells, ultimately inhibit tumour cells’ angiogenesis ( 134 ), which is in agreement with the previously mentioned role of HSPGs as important binding partners and co-receptors of pro-angiogenic factors, including VEGF and FGF. More recently, novel xyloside-derived compounds with potential to be used in therapy for glioblastoma were identified due to their ability of impairing endogenous GAG biosynthesis by binding to XYLT1 and β4GAL T7 active sites, and consequently decreasing glioblastoma cell viability ( 135 ). In a different study, Mani K. et al demonstrated that the use of the synthetic xyloside 2(6-hydroxynaphthyl)-β-D-xylopyranoside inhibited tumour cell growth in vitro , in human lung and hepatocellular carcinoma, and SV40-transformed mouse embryonic fibroblasts 3T3 cells, as well as in vivo , in human bladder carcinoma cells ( 136 ).…”
Section: Targeting Of Hs and Hs Biosynthetic Enzymesmentioning
confidence: 99%
“…By these two mechanisms, xylosides act to block HSPG functions. Xylosides have been shown to inhibit glioblastoma cell viability [ 156 ], glioma cell invasion [ 157 ], tumor angiogenesis in vitro [ 158 ], and various tumor cell line growth in vitro and human bladder carcinoma growth in vivo [ 159 ]. These anti-HSPG strategies and available agents give great potential to future tauopathy treatments, exemplified by a recent study from Naini et al showing that surfen and oxalyl surfen decreased tau hyperphosphorylation and mitigated neuron deficits in vivo in a zebrafish model of tauopathy [ 160 ].…”
Section: Future Studies From the Hspg Aspectmentioning
confidence: 99%